Law, literature, and society in legal texts from Qumran : papers from the ninth meeting of the International Organization for Qumran Studies, Leuven 2016 - Jokiranta, Jutta,; Zahn, Molly M. 1979- (Studies on the Texts of the Desert of Judah, 2019)
Reflecting the increasing recognition of the importance of legal texts and issues in early Judaism, the essays in this collection examine halakhic and rule texts found at Qumran in light of the latest scholarship on text production, social organization, and material culture in early Judaism. The contributors present new interpretations of long-lived topics, such as the sobriquet "seekers of the smooth things," the Treatise of the Two Spirits, and 4QMMT, and take up new approaches to purity issues, the role of the maśkil, and the Temple Scroll. The volume exemplifies the range of ways in which the Qumran legal texts help illuminate early Jewish culture as a whole.